Wielopole wielokrotnie: przestrzenna reżyseria afektu - Pieniążek , Marek (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
The article presents the forms of repetition in the creation and reception of Tadeusz Kantor’s performances. Krakow cellars, Kantor’s home in Wielopole and school class in Bielkowo near Łazy in Pomerania connect here the topic of affective searching and finding sources of identity and memory. The process may refer to both the artist and the viewer, seeking in the memory, art and landscape the traces of himself, recorded in the past and projected onto the surroundings. The author’s discovery of the interiors of the cellars under the floor of the house in Wielopole, similar to the Krzysztofory cellars in Krakow where Kantor conducted the rehearsals of the famous The Dead Class, leads to the conclusion that the preexisting in Wielopole under the floor of a childhood room the space of Kantor’s play can be the source of director’s affective repetition. With the use of the repetition mechanism, numerous further artistic discoveries and meetings of the artist with the self and visions of his future performances have been made. The facilitation of this process for viewers of exhibitions and to the recipients of art, both in Bielkowo and Wielopole, seems to be the inclusion of another tool in theatrical and artistic education.